1970
DOI: 10.3126/on.v7i1.2554
|View full text |Cite
|
Sign up to set email alerts
|

The Birds of Sukla Phanta Wildlife Reserve, Nepal

Abstract: Sukla Phanta Wildlife Reserve lies in the southwest corner of Nepal. It has been listed as an important bird area and a number of bird studies have been conducted here. The reserve is an important refuge especially for many grassland birds, several of which are globally threatened. The high, total of 15 globally threatened and 13 near-threatened bird species occur in Sukla Phanta. Some of the bird species reach their world limit of distribution at Sukla Phanta. Of all the habitats found in Sukla Phanta, grassl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Betana pond is important for aquatic macroflora and faunal habitats in Morang district (Jha et al, 2005;Subba and Thapa, 2005). Available reports on aquatic macrophytes and macro-fauna found in wetlands of eastern Nepal include Surana et al (2004), Jha (2005), Chhetry (2006), Baral and Inskipp (2009). An attempt has been made to study seasonal variations in physico-chemical parameters and diversity of macro-biota in Betana pond, in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Betana pond is important for aquatic macroflora and faunal habitats in Morang district (Jha et al, 2005;Subba and Thapa, 2005). Available reports on aquatic macrophytes and macro-fauna found in wetlands of eastern Nepal include Surana et al (2004), Jha (2005), Chhetry (2006), Baral and Inskipp (2009). An attempt has been made to study seasonal variations in physico-chemical parameters and diversity of macro-biota in Betana pond, in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Chhetry (2006) reported 98 species of wetland birds belonging to 60 genera and 18 families around the Koshi barrage area. Similar study in Suklaphanta National Park found a total of 15 globally threatened and 13 near-threatened bird species where majority of the birds were the wetland dependent birds (Baral and Inskipp, 2009). It indicates that Beeshazari lake system alone supported more species of wetland birds than Rupa, Phewa lake and lower than Jagadishpur reservoir, Koshi barrage and Rapti and Narayani river systems.…”
Section: Diversity Of Wetland Birdsmentioning
confidence: 56%
“…Similar type of study by Sharma (2004) recorded twelve nationally threatened species of birds including two critically endangered birds in the Barandabar corridor forest. Baral & Inskipp (2009) Fishing, livestock grazing pressure and human disturbances were the major threats to the water birds in this area. The abundance of species was greatly affected by the number of fisherman presence for collection of prey species of water birds (e.g., fishes, snails etc.).…”
Section: Fig 4 Correlation Coeffi Cients Obtained From Pca Of Specimentioning
confidence: 99%